Spatial Model of Landslide Hazard in Tarusan Watershed - Yatno, Triyatno Yatno; Iswandi, Iswandi. U Iswandi; Febriandi, Febriandi Febriandi (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
Spatial modeling of landslide hazards in the Tarusan watershed is an effort to reduce losses due to landslide disasters. The purpose of this article is; determine the frequency ratio value of each parameter that causes landslides, and perform spatial modeling of landslide hazards using the frequency ratio method. The method used is a quantitative method with a modeling approach to determine the pixel value based on the frequency ratio. The results of the research show that the largest frequency value is found in the land cover parameter in the form of mixed gardens with an FR value of 2, 10, and rainfall with an FR value of 2.06. Thus, the triggering factors for landslides in the Tarusan watershed are changes in land cover and rainfall. The results of landslide hazard modeling in the Tarusan watershed show a high hazard area of ​​2095.41 ha or 7.39%, a medium hazard area of ​​4148.73 ha or 14.63%, and a low hazard area of ​​22117.46 ha or 77.98%. Key words: hazard, landslide, spatial model